Revision of the genus Epexochus Reitter, with description of three new species (Coleoptera: Curculionidae: Lixinae: Cleonini) - Meregall, Massimo; Talamelli, Fabio (Zootaxa, 2009)
The genus Epexochus Reitter is revised, its morphological characters are defined and the differences from the most closely related genera, Leucochromus Motschulsky and Eurycleonus Bedel, are outlined. All the populations of Epexochus from Kazakhstan and north-western China (Xinjiang) are referred to a single species, E. lehmanni (Ménétries). The status of Exochus latus Chevrolat is discussed and its name is formally synonymised with lehmanni. According to Art. 45.6.4.1 of the ICZN (1999), the name lehmanni var. consobrinus Faust, originally proposed for a colour variant and misidentified by Ter-Minasyan, is deemed to be subspecific and thus a synonym of lehmanni. Three new species are described in the genus: E. korotyaevi sp. n. (type locality: southern Tajikistan, Shaar-tuz region), characterised by the pronotum curved towards the elytra and by slender, lanceolate scales; E. voriseki sp. n. (type locality: central Uzbekistan, Gazli), characterised by small size, only slightly convex elytra and long hair-like setae, and E. mongolicus sp. n. (type locality: western Mongolia, Kobdoskij Aimak), characterised by large size, convex elytra with flat intervals and an elongate lamella of the aedeagus.